Coeliac disease presenting as acute bleeding disorders. Issue 677 (March 1982) - Graham, David R.; Alstead, Elspeth; Bellingham, Alistair J.; Krasner, Neville; Martindale, John
Abstract : Two young women presented with acute bleeding disorders and were subsequently found to have coeliac disease.